Mitochondrial Deacetylase Sirt3 Reduces Vascular Dysfunction and Hypertension While Sirt3 Depletion in Essential Hypertension Is Linked to Vascular Inflammation and Oxidative Stress - Dikalova, Anna E.; Pandey, Arvind; Xiao, Liang; Arslanbaeva, Liaisan; Sidorova, Tatiana; Lopez, Marcos G.; Billings, Frederic T.; Verdin, Eric; Auwerx, Johan; Harrison, David G.; Dikalov, Sergey I. (Circulation research, 2020)
Hypertension represents a major risk factor for stroke, myocardial infarction, and heart failure and affects 30% of the adult population. Mitochondrial dysfunction contributes to hypertension, but specific mechanisms are unclear. The mitochondrial deacetylase Sirt3 (Sirtuin 3) is critical in the regulation of metabolic and antioxidant functions which are associated with hypertension, and cardiovascular disease risk factors diminish Sirt3 level. We hypothesized that reduced Sirt3 expression contributes to vascular dysfunction in hypertension, but increased Sirt3 protects vascular function and decreases hypertension. To test the therapeutic potential of targeting Sirt3 expression, we developed new transgenic mice with global Sirt3OX (Sirt3 overexpression), which protects from endothelial dysfunction, vascular oxidative stress, and hypertrophy and attenuates Ang II (angiotensin II) and deoxycorticosterone acetate-salt induced hypertension. Global Sirt3 depletion in mice results in oxidative stress due to hyperacetylation of mitochondrial superoxide dismutase (SOD2), increases HIF1α (hypoxia-inducible factor-1), reduces endothelial cadherin, stimulates vascular hypertrophy, increases vascular permeability and vascular inflammation (p65, caspase 1, VCAM [vascular cell adhesion molecule-1], ICAM [intercellular adhesion molecule-1], and MCP1 [monocyte chemoattractant protein 1]), increases inflammatory cell infiltration in the kidney, reduces telomerase expression, and accelerates vascular senescence and age-dependent hypertension; conversely, increased Sirt3 expression in Sirt3OX mice prevents these deleterious effects. The clinical relevance of Sirt3 depletion was confirmed in arterioles from human mediastinal fat in patients with essential hypertension showing a 40% decrease in vascular Sirt3, coupled with Sirt3-dependent 3-fold increases in SOD2 acetylation, NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) activity, VCAM, ICAM, and MCP1 levels in hypertensive subjects compared with normotensive subjects. We suggest that Sirt3 depletion in hypertension promotes endothelial dysfunction, vascular hypertrophy, vascular inflammation, and end-organ damage. Our data support a therapeutic potential of targeting Sirt3 expression in vascular dysfunction and hypertension.